Primary Multifocal Recurrent Urinary Bladder Amyloidosis: A Rare Case Report from Syria - Leen Jamel Doya; Lama Doya; Khaled Al-Yousef; Ali Adib; Abedallah Al Shamali; Basel Al Deeb; Mohamad Kanan (Case Reports in Medicine)
Primary urinary bladder amyloidosis is a rare disorder of protein metabolism characterized by the extracellular deposition of fibrillin. To date, fewer than 200 cases have been reported in the literature. We herein present a case of 59-year-old female with primary multifocal recurrent urinary bladder amyloidosis. The patient was treated with a new method (laser therapy) mentioned for the first time in the literature. After 18 months of treatment, the patient has no complaints. Our case illustrates a new procedure in the treatment of primary multifocal bladder amyloidosis.